Young American Muslims: Dynamics of identity - Kabir, Nahid Afrose (© 2013 Edinburgh University Press, 2019)
This book was published by Edinburgh University Press, 2013. The publisher's website is at: https://edinburghuniversitypress.com/book-young-american-muslims.html